Search for a W ' boson decaying to a tau lepton and a neutrino in proton-proton collisions at root s=13 TeV - Sirunyan, A. M.; Tumasyan, A. R.; Adam, Wolfgang; Ambrogi, Federico; Asilar, Ece; Md. Ali, Mohd. Adli (Elsevier B.V., 2019)
A search for a new high-mass resonance decaying to a τ lepton and a neutrino is reported. The analysis uses proton-proton collision data collected by the CMS experiment at the LHC at √s = 13 TeV, corresponding to an integrated luminosity of 35.9 fb−1. The search utilizes hadronically decaying τ leptons. No excess in the event yield is observed at high transverse masses of the τ and missing transverse momentum. An interpretation of results within the sequential standard model excludes W boson masses below 4.0 TeV at 95% confidence level. Existing limits are also improved on models in which the W boson decays preferentially to fermions of the third generation. Heavy W bosons with masses less than 1.7–3.9 TeV, depending on the coupling in the non-universal G(221) model, are excluded at 95% confidence level. These are the most stringent limits on this model to date